MAIN FACTORS AFFECTING ECONOMIC GROWTH IN THE COUNTRY AND THEIR DYNAMICS - Saitov, Sirojiddin; Tuychieva, Nodira (Science technology&Digital finance, 2023)
The article considers economic growth as an economic category, its types and factors affecting it. All countries of the world are classified according to the level of development in terms of industrial economic growth.